BEBAN PENCEMARAN DETERJEN KELURAHAN TAMBAK WEDI KECAMATAN KENJERAN KOTA SURABAYA - Edza Aria Wikurendra; Iva Rustanti; A. T Diana Nerawati (Poltekkes Kemenkes Surabaya, 2014)
The increasing use of detergents as cleaning agents in the community potentially results in thepollution of the water bodies, this condition worsened by the quality of water from wells having a highmineral hardness. When cleaning agents flow into the rivers, it induces negative impact on theenvironment and eventually upon health. Resultsof the observation showed that pollutant loads that camefrom the use of detergent in 55 households was at 0.323 mgjltjmonth or 5,924 mgjday, while thestandard maximum pollutant load of detergent waste is 0.0016 mgjltjmonth or 0.0292 mgjday. The studyconcluded that the pollutant load value was higher than the maximum pollutant load value, suggestingthat pollutant load of detergent waste provided high contribution to pollution of the land and waters in thearea, thereby diminishing the surface water quality as well as ground water quality, marked by incidencesof diseasessuch as diarrhea, heavy metal poisoning and skin diseases.Therefore, it is recommended thathouseholds should use environment-friendly detergents because of its biodegradable properties. They areencouraged to make simple domestic waste treatment equipment using biofilter technique